2018
DOI: 10.1097/md.0000000000012142
|View full text |Cite
|
Sign up to set email alerts
|

Is percutaneous pinning needed for the treatment of displaced distal radius metaphyseal fractures in children?

Abstract: Background:Distal radius metaphyseal (DRM) fractures are very frequent childhood fractures. Whether additional percutaneous pinning improves the outcome remains controversial. In this review, we tried to systematically evaluate the effect of percutaneous pinning on re-displacement, secondary reduction, radiographs, function, and complications in children with displaced DRM fractures.Methods:PubMed, Medline, Embase, Cochrane Library, and Web of Science databases were explored systematically to identify randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…In a systematic review, the mean re-displacement rate was reported 40% in the casting group and 3.6% in the pinning group [11]. K-wire xation of displaced distal radius fractures in children reduced their predicted failure rate from 14-60% was reported by Choi et al [10].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a systematic review, the mean re-displacement rate was reported 40% in the casting group and 3.6% in the pinning group [11]. K-wire xation of displaced distal radius fractures in children reduced their predicted failure rate from 14-60% was reported by Choi et al [10].…”
Section: Discussionmentioning
confidence: 89%
“…Although the advantages of K-wires are known, there are some complications related to K-wires which were reported in literatures [11,12]. In some studies, pining complication rates were varying from 0-38% (median 8.3%) [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes practice variation occurs even when high-quality evidence exists (Grove et al 2016 , Lohmander et al 2016 ). For the fractures discussed here, there are no published low-risk-of-bias comparative trials that have compared cast-only treatment with closed reduction alone, or closed reduction and percutaneous fixation (Handoll et al 2018 , Zeng et al 2018 ). Evidence from such trials would be helpful, and would need to cover the “grey zone” where most practice variation is likely to occur.…”
mentioning
confidence: 99%